Carole Lambert (ed): Du manuscrit à la table - Davidson, Alan E (Petits Propos Culinaires, 1993)
Carole Lambert (ed): Du manuscrit à la table: Champion/Slatkine, Paris, and Les Presses de l’Université de Montréal, 1992: 392 pp, Canadian 39.00 (may be ordered from the Canadian distributor, Gaatan Morin, C P 180, Boucherville (QC), Canada J4B 5E6- tel (514) 449 7886- adding 10% for postage).